Integrative taxonomy of Cercomacroides serva (Sclater, 1858) demonstrates the validity of C. hypomelaena (Sclater, 1890) comb. nov. (Aves: Thamnophilidae) - Vagner Cavarzere; Luís F. Silveira (Vertebrate Zoology, 2024)
Abstract Cercomacroides serva is widely distributed in northern South America. However, this species has never been thoroughly evaluated taxonomically. We conducted a taxonomic study of three taxa currently classified under Cercomacroides serva, based on a study of 307 skins and 145 recordings of male loudsongs. Females from the northwest Amazonian population differ qualitatively from populations from the southwest Amazon in the coloration of the upperparts, primary, and tail. Male loudsongs are superficially similar between these two populations, but the shape of the notes differs significantly. There is no evidence of intergradation or clinal variation in female plumage or male loudsongs. Based on differences in plumage coloration, loudsongs, and lack of evidence of intergradation, we suggest that two species are best recognized. The name Cercomacroides serva is here restricted to populations north of the Marañon River in Peru, to the north in Ecuador, and in southwestern Colombia. The name Cercomacroides hypomelaena comb. nov. is revived. This species is found south of the Marañon River, and on both banks of the Ucayali River in Peru, to the eastern left bank of the Madeira River in Brazil, and in northern Bolivia.